The Effects of Learning Provision by Using Multimedia Activity Package with Role Play to Promote Self-Esteem in Young Children - Noiman, Korawit; Lehmongkol, Pattamavadi (Interdisciplinary Academic and Research Journal, 2023)
The management of learning by using a series of mixed media activities and role-plays for children to demonstrate their abilities. It is a creative activity that results in early childhood development in terms of physical, emotional, social, and intellectual development. It is also an ethical learning that helps children discover themselves, understand themselves, and can project their future. Thus, this study aims to study the effects of learning provision by using a multimedia activity package with role play to promote self-esteem in young children. The target group was 16 male and female young children aged between 5-6 years old, studying in kindergarten level 3 in semester 2 of the academic year 2022, Banmabfugtong School, Huay Yai sub-district, Banglamung district, Chonburi province under Chonburi Primary Educational Service Area Office 3, The research instrument included 24 plans of learning experience provision using multimedia activity package with role play and an assessment form on self-esteem in young children. The quantitative data were analyzed by mean and standard deviation. The qualitative data were analyzed by content analysis. The research findings revealed that young children who participated in learning experience provision with a multimedia activity package with role play had higher mean scores of self-esteem than those who did not. The highest mean scores were self-confidence and self-esteem, respectively.